Transport and magnetoresistance studies on polycrystalline La0.4Dy0.1Ca0.5MnO3: Role of phase separation. (1st June 2017) - Krichene, A.; Boujelben, W.; Mukherjee, S.; Solanki, P.S.; Shah, N.A.
Abstract: Electrical and magnetoresistive response of phase–separated La0.4 Dy0.1 Ca0.5 MnO3 polycrystalline bulk sample has been investigated. The magnetic structure below 25 K is identified as a coexistence of ferromagnetic, strong antiferromagnetic and weak metastable antiferromagnetic domains. The irreversibility in the electrical resistivity with magnetic field cycling is associated to the training effect. The resistivity in the metallic range for μ0 H ≤ 4 T follows Zener polynomial law with unusual values of n exponent due to the high spin fluctuations. Temperature dependence of magnetoresistance (MR) exhibits a plateau–like shape for μ0 H ≤ 2 T. For MR(T), maximum MR ∼ 98.8% under 2 T field at 77 K and for MR(H), MR is about 90.5% under 1 T magnetic field at 75 K has been recorded. The colossal values of MR suggest the possibility of using our sample for technological applications. An enhancement of MR(H) at 75 K was observed in the field range 0–2 T due to magnetic field cycling. The spectacular behavior of resistivity for La0.4 Dy0.1 Ca0.5 MnO3 sample is essentially attributed to phase separation phenomenon. Graphical abstract: Image